Expanding the Egbenema horizon: Novel species discovery in India and first complete genome assembly of the genus - Bhagat, Jayesh M.; Khilari, Ajinkya A.; Shanmugam, Dhanasekaran; Patankar, Meena (Algal Research-Biomass Biofuels and Bioproducts, 2025)
The recognition of Egbenema bharatensis, a novel species of cyanobacteria from the Northern Western Ghats, extends the ecological and phylogenetic understanding of the genus Egbenema and highlights terrestrial microbial diversity of the region. Morphological characterization revealed resemblance with other Egbenema species but was inconclusive for definitive taxonomic classification. Preliminary phylogenetic analysis based on 16S rRNA gene sequences indicated affiliation with the genus but showed less than 98 % similarity to known species, pointing toward taxonomic distinctiveness. Analysis of the 16S-ITS region further supported this differentiation, revealing unique secondary structural features. Based on these findings, we propose the isolate as a novel species within Egbenema. Whole-genome sequencing provided full resolution and functional genome annotation revealed nitrogen fixation, cobalamin biosynthesis, and stress tolerance pathways, suggesting its metabolic versatility and potential biotechnological applications. The presence of multiple toxin-antitoxin systems also reflects its adaptability to environmental fluctuation. This study also presents the first complete genome of the genus Egbenema, filling a significant gap in cyanobacterial genomic resources. These findings encourage integrative taxonomic practices and affirm the significance of exploring biodiversity hotspots for uncovering cryptic microbial diversity with ecological and industrial potential.
Keywords: 16S rRNA; Biodiversity hotspots; Cyanobacteria; Egbenema bharatensis; ITS secondary structure; Northern Western Ghats; whole-genome sequencing